The galleys of the kingdom of Sicily: manufacture and supply under the Charles II' reign (Estudios de Historia de España, 2020)
The reign of Charles II was characterized by the fear to the expansion of the Crown of France in the Mediterranean. The defense of the Italians domains of the Hispanic Monarchy relied on the Kingdom of Sicily, whose fleet was an essential piece of the defensive system of the island. In this way, this article is focused in the interventions carried out by the viceroys in order to increase the number of galleys, as well as to resolve their problems of supply with the objective of hindering the Louis XIV’s expansionist interests.
Keywords: Charles II of Spain; Mediterranean; Sicily; Defense; Galleys